2009
DOI: 10.2298/hel0951065c
|View full text |Cite
|
Sign up to set email alerts
|

Wild species of Helianthus L.: Sources of resistance to the parasite Orobanche cumana Wallr.

Abstract: Accessions from different Helianthus species, cultivated sunflower forms and interspecific hybrid forms and lines were included in this investigation. It was established that broomrape resistance was transferred from 11 perennial Helianthus species to interspecific hybrids developed on the basis of new sunflower lines. Some of the new lines possessed other desirable agronomical characters, which could be successfully transferred to new sunflower hybrid cultivars. Differences were observed in the origin of broo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 2 publications
0
9
1
Order By: Relevance
“…Recently, attempts to unravel events that have occurred between annual Helianthus and cultivated sunflower have been studied using interspecific crosses (Kim and Rieseberg 1999;Burke et al 2004;Strasburg and Rieseberg 2008;Sujatha et al 2008;Heesacker et al 2009). Serieys (1987), Jan et al (2006), Christov et al (2009), andŠkorić et al (2010) reported many trait transfers from perennial Helianthus, just a few of molecular study has been published on the localization of introgression fragments between common sunflower and perennial Helianthus. In practice, lines carrying one or a few introgression fragments from diverse wild Helianthus have been produced without selection pressure, but only by screening segregating progeny for some agronomic traits such as seed size and oil yield (Serieys 1987).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, attempts to unravel events that have occurred between annual Helianthus and cultivated sunflower have been studied using interspecific crosses (Kim and Rieseberg 1999;Burke et al 2004;Strasburg and Rieseberg 2008;Sujatha et al 2008;Heesacker et al 2009). Serieys (1987), Jan et al (2006), Christov et al (2009), andŠkorić et al (2010) reported many trait transfers from perennial Helianthus, just a few of molecular study has been published on the localization of introgression fragments between common sunflower and perennial Helianthus. In practice, lines carrying one or a few introgression fragments from diverse wild Helianthus have been produced without selection pressure, but only by screening segregating progeny for some agronomic traits such as seed size and oil yield (Serieys 1987).…”
Section: Introductionmentioning
confidence: 99%
“…H. mollis displays resistance to most sunflower pathogens (Atlagić et al 1995) and to the broomrape parasite (Orobanche cumana Wallr.) as all perennial Helianthus species (Jan and Fernandez-Martinez 2002;Christov et al 2009). Thus, sexual combination of sunflower and H. mollis could lead to plants that combine the most valuable traits of each species such as one stem and all agronomic traits from sunflower, with sessile leaves or shorter petioles, as disease tolerance or resistance from H. mollis.…”
Section: Introductionmentioning
confidence: 99%
“…Broomrape resistance, Sclerotinia resistance (Christov et al, 2009), downy mildew resistance (Christov, 2008;Christov et al, 2009), fertility restoration genes, early maturing (Christov, 2008), powdery mildew resistance (Kaya, 2014), sunflower moth (Homoeosoma electellum Hulst) resistance (Vear, 2011) Helianthus hirsutus Raf. Broomrape resistance, Sclerotinia resistance (Christov et al, 2009), downy mildew resistance (Christov, 2008;Christov et al, 2009), fertility restoration genes (Seiler, 1991(Seiler, , 2000Christov, 2008), acidic soil tolerance (Kantar et al, 2015), Alternaria leaf spot [Alternaria helianthi (Hansf.) Tubaki and Nishihara] resistance, stem weevil (Cylindrocopturus adspersus LeConte) resistance (Vear, 2011), Phomopsis brown stem canker (Vear, 2011;Kaya, 2014), tobacco caterpillar (Spodoptera litura Fab.)…”
Section: Accumulated Production Valuementioning
confidence: 99%
“…Different ways for controlling parasite were tested (different methods of soil cultivation, herbicides use, biological agents, etc. ), which gave results (Christov et al, 2009). The resistance to races (A, B, C, D and E) is controlled by single dominant genes (Or 1 , Or 2 , Or 3 , Or 4 and Or 5 ).…”
Section: Introductionmentioning
confidence: 98%